Choose to Share, 4 sponsors provide assistance to UMPSA students - Siti Nur Azwin, Ibrahim (UMPSA, 2024)
PEKAN, 11 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received contributions from four main sponsors during the Choose to Share Handover Ceremony organised by Yayasan UMPSA, held at the Banquet Hall, UMPSA Pekan.